Hubungan antara Street Smart dan Keterampilan Mengajar Mahasiswa PGMI IAIN Curup - Andesmani, Yola; Zulaiha, Siti; Meldina, Tika; Riyan Oktori, Agus (Diksi: Jurnal Pendidikan dan Literasi, 2025)
This study started from the problem of students who felt that their teaching skills were not optimal. Even though students had studied the basics of teaching skills. Then, street smart as a concept of intelligence obtained from experience can play a role in teaching skills. Because street smart is a form of intelligence in addition to academic knowledge. This study aims to include: 1) Street smart of PGMI IAIN Curup students, 2) Pursuing skills of PGMI IAN Curup students, 3) The relationship between street smart and teaching skills of PGMI IAIN Curup students. The research method used is quantitative correlation. The research sample used 60 students. The results of the study showed that overall the data generated from the questionnaire as a research instrument showed a positive relationship between the two variables, then compared with rtable with a significance level of 5% with 60 respondents, rtable was obtained at 0.254. It is proven that rcount is greater than the rtable value (0.565> 0.254).